Rectus Abdominis Endometrioma after Caesarean Section - Igor Mishin; Anna Mishina; Sergiu Zaharia; Gheorghe Zastavnitsky (Case Reports in Surgery)
Isolated rectus abdominis muscle endometriosis is very uncommon with less than 20 case reports being published to date since its first description in 1984 by Amato and Levitt. We report another case of isolated rectus abdominis endometriosis in a 37-year-old patient with a previous caesarian section. We also discuss the diagnostic and treatment particularities in these patients. In our case, the treatment was only surgical and currently the patient is disease-free during the 24-month follow-up.